Development of analytical techniques for probing the effects of -haematin inhibiting compounds on the malaria parasite Plasmodium falciparum - Maepa, Makgalanoto (Department of Medicine, 2024)
Phenotypic screening for novel compounds that inhibit the growth of the malaria parasite remains one of the most effective ways to identify novel antimalarial drugs. Subsequent deconvolution of the drug target and mechanism of action (MoA) are a vital part of the drug development process. This is often a limitation since the appropriate assays can be expensive, time-consuming, or inconclusive. One of the primary MoAs of the clinically approved antimalarials against Plasmodium falciparum is via the inhibition of haem detoxification. Drugs with this MoA, including chloroquine and amodiaquine, exert their therapeutic effect by disrupting haemozoin formation, which leads to increased accumulation of cytotoxic haem. Typically, the activity of potential haemozoin inhibitors is assessed using an in vitro detergentmediated β-haematin inhibition assay. However, this is inadequate for identifying true wholecell inhibitors of haemozoin since the assay is performed extracellularly. The intracellular pyridine-based assay by Combrinck et al. is used to determine whether prioritised β-haematin inhibitors cause significant dose-dependent increases in unsequestered haem (free haem) in the parasite. However, this assay has limitations and disadvantages in terms of its low throughput and the use of toxic reagents. In addition, this method is not readily transferable to other malaria drug discovery laboratories because of the need for specific knowledge of haem chemistry, highly specialised training, and given the labour-intensive nature of the assay. Therefore, developing improved assays that are readily accessible with increased throughput will lead to substantial progress in this area. It is also notable that the processes by which haem kills the parasite are not fully understood and hence the understanding of the effects caused by the unsequestered haem levels in the parasite needs considerable advancement. Consequently, in this work, a novel 96-well plate HPLC-DAD cellular haem fractionation method was developed and validated for quantifying intracellular haem species in the P. falciparum cell. The technique has eliminated the use of toxic pyridine to complex haem for the detection of unsequestered haem. Instead, it uses non-volatile imidazole for complex formation and has also reduced parasite starting material four-fold compared with the original method. Furthermore, this 96-well plate method allows the simultaneous evaluation of four test compounds at five selected concentrations, instead of only one test compound per 24- well plate. The assay was validated against the original pyridine-based method using four known haemozoin-inhibiting drugs, including chloroquine, amodiaquine, lapatinib and lomitapide, as well as four known non-inhibiting haemozoin drugs, including mefloquine, Abstract lumefantrine, pyrimethamine and tetrahydrocannabinol (THC). This higher throughput cellular fractionation assay will significantly increase throughput while also becoming an invaluable technique for probing haemozoin inhibition as a relevant MoA for new compounds in antimalarial drug discovery pipelines. Following successful validation of the 96-well four-compound cellular haem assay, the method was modified to a 96-well 33-compound qualitative high-throughput haem fractionation assay. Applications of the high-throughput method are intended to provide a valuable technique to accommodate the standard high-throughput screening campaigns that focus on identifying haemozoin-inhibiting molecules. Thus, this qualitative high-throughput assay enabled the quantifying of intracellular haem species in P. falciparum cells for 33 compounds tested simultaneously at a single-point concentration corresponding to 2x the 50% inhibitory concentration (IC50). The compounds used to validate the assay consisted of known haemozoin inhibitors, non-haemozoin inhibitors, and novel experimental compounds sourced from different drug discovery projects at the University of Cape Town. Notably, ten of the experimental compounds were from a high-throughput screening campaign to identify βhaematin inhibiting compounds, which were invaluable for proof-of-concept application. In order to further validate the single-point results for these compounds, four (one predicted to be a non-haemozoin inhibitor and three to be haemozoin inhibitors) of this set were chosen to evaluate the method's haemozoin inhibition predictive capability using a full-dose response approach. By employing the 96-well HPLC-DAD four-compound method, we demonstrated that the single-point 33-compound high-throughput haem fractionation assay could correctly classify all four experimental compounds and the known antimalarial drugs as haemozoin or non-haemozoin inhibitors. These findings are substantial, as the validated 33-compound highthroughput assay can be used in conjunction with the extracellular β-haematin method during MoA studies for newly developed or existing compounds. This is even in cases when haemozoin inhibition is not the desired drug target, as those which cause increased unsequestered haem levels can be eliminated from further progression. After investigating a diverse series of haemozoin-inhibiting compounds using the cellular haem fractionation methods, we discovered that each compound exhibited varying levels of unsequestered haem in the parasite at their relevant IC50. Surprisingly, more active compounds (lower IC50 values) often produced lower levels of unsequestered haem than less active ones (higher IC50 values). These observations imply that the common notion that haemozoin inhibitors cause an accumulation of unsequestered haem, which directly leads to parasite death, does not hold. If this were to be the case, the unsequestered haem levels Abstract would be expected to be the same at the IC50 of each compound. This prompted an investigation of the toxicity and effect of unsequestered haem on the parasite. A flow cytometry assay was developed to investigate the killing speed and the stage-specific effects of the various haemozoin-inhibiting compounds. The findings show that compounds that produce lower levels of unsequestered haem tend to kill the parasites earlier in the life cycle. In contrast, those compounds that exhibit higher levels of unsequestered haem tend to kill later in the life cycle. Furthermore, it was also observed that the surviving parasite population postcompound incubation differed. Compounds releasing lower levels of unsequestered haem resulted in a less mature parasite population, while those releasing higher levels of unsequestered haem resulted in a more mature parasite population. These results suggest that the toxicity of haem is compound-specific. This leads to the hypothesis that the compounds present as haem–inhibitor complexes and that haemozoin inhibitors act as complexes exerting unique activities. This has important implications for the study and the design of future hemozoin-inhibiting antimalarial drugs, as well as for our understanding of parasite resistance mechanisms.